2012
DOI: 10.1007/s00262-012-1326-1
|View full text |Cite
|
Sign up to set email alerts
|

Memory T cells are uniquely resistant to melanoma-induced suppression

Abstract: We have previously observed that in vivo exposure to growing melanoma tumors fundamentally alters activated T cell homeostasis by suppressing the ability of naïve T cells to undergo antigen-driven proliferative expansion. We hypothesized that exposure of T cells in later stages of differentiation to melanoma would have similar suppressive consequences. C57BL/6 mice were inoculated with media or syngeneic B16F10 melanoma tumors 8 or 60 days after infection with lymphocytic choriomeningitis virus (LCMV), and spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Adoptive cell transfer was performed as previously described [21, 22]. Naïve CD8+ GP33-specific T cells were derived from splenocytes harvested from Ly5.1+ P14 TCR transgenic mice (C57BL/6 background with TCR specificity for GP33).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adoptive cell transfer was performed as previously described [21, 22]. Naïve CD8+ GP33-specific T cells were derived from splenocytes harvested from Ly5.1+ P14 TCR transgenic mice (C57BL/6 background with TCR specificity for GP33).…”
Section: Methodsmentioning
confidence: 99%
“…However, the specific consequences of effector versus memory T cell transfer on the intratumoral and systemic immunological milieu and on endogenous tumor-directed T cell responses have not been clearly dissected. We have previously demonstrated that in vivo exposure to melanoma impairs the transition of resting to effector T cells and enhances the apoptotic contraction of acutely activated T cells CD8+ T cells [20, 21]; in contrast, the capacity of memory T cells for homeostatic proliferation and antigen-driven reactivation are unaltered by in vivo exposure to melanoma [22]. …”
Section: Introductionmentioning
confidence: 99%
“…Adoptive cell transfer as performed as previously described (9). Briefly, splenocytes were harvested from Ly5.1+ B6.SJL mice 8 days after LCMV infection, then enriched for CD8 expression using magnetic bead separation columns (Miltenyi, Auburn, CA).…”
Section: Methodsmentioning
confidence: 99%
“…Lymphocytes were stained with APC-labeled MHC class I (D b ) tetramers loaded with GP33, PErCp-labeled anti-CD8, PE-labeled anti-Ly5.1, and FITC-labeled anti-CD44 antibodies. Flow cytometric analysis of splenocytes was performed on day 9 or 14 after B16GP33 tumor inoculation using methods previously described (9-12). Briefly, freshly harvested splenocytes (10 6 cells/well) were stimulated with (or, as a negative control, without) GP33 at a concentration of 0.1 μg/mL in the presence of brefeldin A and human recombinant IL-2 (10 U/well) at 37°C for 5 hours in flat-bottomed 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation